Ni-Nb-Zr metastable phases formation, a thermodynamic and chemical approach. - Deo, Leonardo Pratvieira (Eclética Química, 2022)
Gibbs’ free energy of formation is considered a good guidance in order to describe or predict the phases formation within the standard state; however, many materials are produced out of their equilibrium conditions, and consequently, metastable phases are formed. There is no universal knowledge related to metastable phases formation; therefore, this paper presents considerations in order to elucidate some understanding about two metastable phases found in a rapid quenched alloy from Ni-Nb-Zr system during the solidification process. The analyzed alloy, namely Ni61.6Nb33.1Zr5.3 (at.%) was previously synthesized and characterized in two previous works. The hypotheses presented here consider free energies of formation among phases which compete to nucleate, stability of crystalline phases at nanoscale and atomic pair preferences during the nucleation. The understanding related to metastable phases formation may produce and improve promising technological materials.